Bone histology
1 online resource (xv, 481 pages)
Keywords: "Bone Histology: A Biological Anthropological Perspective, Second Edition builds on the success of the first edition, recognizing the significant advances that have occurred in bone biology, histology, and histological techniques and methods in subsequent years. Bones and teeth are of considerable importance for anthropological and related research, due to their nature as hard tissues. The physical remains of humans available to biological anthropologists, bioarchaeologists, paleopathologists, and paleontologists are, with exception to forensic anthropology, limited to skeletal material; fortunately, the same characteristics of hard tissues that lead to their persistence after death make them a storehouse of information about biological processes experienced during the life of the individual. This book covers important aspects of bone biology which underlie the microstructure of hard tissues that are crucial for histological analysis. This includes an overview of two major metabolic processes, bone remodelling and modelling, and their importance for understanding and interpreting bone histomorphology. Subsequent chapters apply histological methods to the biological profile, such as estimation of age and evaluation of pathological conditions that affect the skeleton, or to determine whether remains are human or nonhuman. Finally, there is a discussion of current research trends in bone histology, with a focus on technological advances in imaging and methods. Reviews of four well-documented skeletal collections-developed specifically for bone histological and imaging research-are discussed, as well as, the importance of such collections for future research. Bone Histology, Second Edition has assembled a collection of contributing authors, with extensive experience and expertise in various aspects of hard tissue biology, to provide readers with an overview of the current state of research and potential applications of histological analysis in biological anthropology, forensic anthropology, and skeletal biology. It serves as a valuable resource for students, researchers, and practitioners in these and related disciplines"--